Mission-Critical Security Planner: When Hackers Won't Take No for an Answer - Greenberg, Eric (Wiley Publishing, 2011)
Shows step-by-step how to complete a customized security improvement plan, including analyzing needs, justifying budgets, and selecting technology, while dramatically reducing time and cost Includes worksheets at every stage for creating a comprehensive security plan meaningful to management and technical staff Uses practical risk management techniques to intelligently assess and manage the network security risks facing your organization Presents the material in a witty and lively style, backed up by solid business planning methods Companion Web site provides all worksheets and the security planning template